Parental Involvement In Learners’ Education: Teachers’ Perceptions and Home School Partnership Practices - Delfinado, Jolly; Vergara, Florante (Studies in Technology and Education, 2026)
Parental involvement plays a crucial role in supporting learners’ academic achievement, behavioral development, emotional well-being, and school engagement. This qualitative study explored teachers’ perceptions and school–home partnership practices regarding parental involvement in learners’ education in Cordon North and South Districts, Schools Division of Isabela. Utilizing a phenomenological qualitative research design, the study examined how teachers perceive parental participation, implement school–home partnership initiatives, and address challenges related to family engagement in elementary education. Data were gathered through semi-structured interviews, focus group discussions, classroom observations, and document analysis involving fifteen purposively selected public elementary school teachers. Thematic analysis following Braun and Clarke’s framework was employed in analyzing the data. Findings revealed five major themes: (1) Parental Involvement as a Foundation of Learner Success and Motivation; (2) Communication and Collaborative School–Home Relationships; (3) Shared Responsibility and Community Participation in Education; (4) Challenges in Sustaining Meaningful Parental Engagement; and (5) Teacher Initiative, Flexibility, and Partnership-Building Strategies. Participants emphasized that active parental involvement positively influenced learners’ academic performance, classroom behavior, attendance, confidence, and motivation to learn. Teachers also highlighted the importance of regular communication, mutual trust, and collaborative school activities in strengthening school–home relationships. However, participants encountered challenges related to parents’ work schedules, economic constraints, limited educational background, communication barriers, and inconsistent parental participation. Despite these challenges, teachers demonstrated adaptability and commitment in sustaining meaningful family engagement through flexible communication strategies and community-based collaboration. The study concludes that strong school–home partnerships significantly contribute to learner development and educational success. Findings provide implications for family engagement programs, educational leadership, community participation, and policy initiatives promoting collaborative partnerships between schools and families.